Pengembangan wellness programs dalam meningkatkan kebugaran fisik dan profil metabolik karyawan - Weni Kurdanti; Rini Wuri Astuti; Herni Endah Widyawati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2026)
Effectiveness of wellness programs on physical fitness and metabolic profile of employeesBackground: Non-communicable diseases (NCDs) in Indonesia, especially among employees, are on the rise due to lifestyle changes. Wellness programs in the workplace have the potential to be an effective strategy for NCD prevention through changes in dietary behavior, physical activity, and holistic health management. Objective: This study aims to evaluate the effectiveness of wellness programs on employees' body composition, physical fitness, dietary intake, and metabolic profile. Methods: A quasi-experimental study with a non-equivalent control group design was conducted over 12 weeks among 41 employees with a BMI ≥25.0 kg/m². The intervention group received nutrition education and treadmill-based physical exercise for 30–45 minutes, 3 times per week, while the control group received only nutrition education. Body composition was measured using bioelectrical impedance analysis, and physical fitness was assessed via the Bruce treadmill test (VO₂max). Analyses employed repeated-measures ANOVA and the Friedman test (p < 0.05). Results: The intervention group showed a significant decrease in body fat percentage (p=0.014) and subcutaneous fat (p=0.008), and an increase in skeletal muscle mass (p=0.018). Fat intake also differed significantly between groups (p=0.004). Total cholesterol decreased significantly in both groups (p=0.001). There were no significant differences in body weight, BMI, blood glucose, blood pressure, visceral fat, body water content, and bone density (p>0.05). Fitness improved significantly within the groups (p<0.05), but not between groups (p>0.05). Conclusions: Wellness programs that combine nutrition education and physical exercise improve body composition and lipid profiles, but do not significantly change body weight or other biochemical parameters within 12 weeks. These findings suggest that the clearest benefit is in body composition and lipid profile.